Calcineurin B homologous protein 3 binds with high affinity to the CHP binding domain of the human sodium/proton exchanger NHE1. Issue 1 (December 2018) - Fuchs, Simon; Hansen, Sierra; Markones, Marie; Mymrikov, Evgeny; Heerklotz, Heiko; Hunte, Carola
Abstract The Na+ /H+ exchanger NHE1 is critical for cell vitality as it controls intracellular pH and cell volume. Its functionality is influenced by calcineurin B homologous proteins (CHPs). The human isoform CHP3 is important for transport of NHE1 to the plasma membrane and for its activity. Here, we characterized the binding interaction of human CHP3 with the regulatory domain of NHE1. The exact binding site of CHP3 was previously debated. CHP3 as well as both regions of NHE1 in question were produced and purified. CHP3 specifically formed stable complexes with the CHP-binding region (CBD) of NHE1 (residues 503–545) in size-exclusion chromatography (SEC), but not with the C-terminal region (CTD, residues 633–815). CTD was functional as shown by Ca2+ -dependent binding of calmodulin in SEC analysis. CHP3 bound with high affinity to CBD with an equilibrium dissociation constant (K D ) of 56 nM determined by microscale thermophoresis. The high affinity was substantiated by isothermal calorimetry analysis (K D = 3 nM), which also revealed that the interaction with CBD is strongly exothermic (ΔG° = −48.6 kJ/mol, ΔH = −75.3 kJ/mol, −TΔS° = 26.7 kJ/mol). The data provide insights in the molecular mechanisms that underlie the regulatory interaction of CHP3 and NHE1 and more general of calcineurin homologous proteins with their target proteins.